2014
DOI: 10.1002/2014jb010987
|View full text |Cite
|
Sign up to set email alerts
|

Latest Quaternary paleoseismology and evidence of distributed dextral shear along the Mohawk Valley fault zone, northern Walker Lane, California

Abstract: The dextral-slip Mohawk Valley fault zone (MVFZ) strikes northwestward along the eastern margin of the Sierra Nevada in the northern Walker Lane. Geodetic block modeling indicates that the MVFZ may accommodate~3 mm/yr of regional dextral strain, implying that it is the highest slip-rate strike-slip fault in the region; however, only limited geologic data are available to constrain the system's slip rate and earthquake history. We mapped the MVFZ using airborne lidar data and field observations and identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Within the Basin and Range Province and, in particular, the Walker Lane belt, discrepancies commonly exist between geodetically determined strain rates and slip rates determined from geologic measurements along component range-bounding faults (e.g., Bormann et al, 2016;Gold et al, 2014;Herbert et al, 2013;Lifton et al, 2013;Personius et al, 2017, Wesnousky et al, 2005. This study, like many previous reports, emphasizes the fact that geodetic strain rates do not necessarily reflect long-term slip rates on discrete faults.…”
Section: Discussionsupporting
confidence: 50%
“…Within the Basin and Range Province and, in particular, the Walker Lane belt, discrepancies commonly exist between geodetically determined strain rates and slip rates determined from geologic measurements along component range-bounding faults (e.g., Bormann et al, 2016;Gold et al, 2014;Herbert et al, 2013;Lifton et al, 2013;Personius et al, 2017, Wesnousky et al, 2005. This study, like many previous reports, emphasizes the fact that geodetic strain rates do not necessarily reflect long-term slip rates on discrete faults.…”
Section: Discussionsupporting
confidence: 50%
“…In sum, it appears that dextral shear has been more or less equally distributed across the central Walker Lane throughout the late Quaternary and that the locus of slip temporally transfers within the system of strike-slip faults of this study. This pattern of equally distributed and temporally variable strain release may be common throughout the Walker Lane (e.g., Frankel et al, 2011;Gold et al, 2014). The Walker Lane has been interpreted as an incipient plate boundary (Faulds et al, 2005), and shown to be relatively structurally complex when compared to the San Andreas (Wesnousky, 2005b), the main plate boundary fault between North America and the Pacific plate (Fig.…”
Section: Comparing Geologic and Geodetic Slip Ratesmentioning
confidence: 96%
“…The Northern Walker Lane encompasses the northwest‐striking dextral strike‐slip Pyramid Lake (Angster et al., 2016; Briggs, 2004), Warm Springs (Chupik, 2019; R. Gold et al., 2013), Honey Lake (R. D. Gold et al., 2017), Polaris (Hunter et al., 2011), and Mohawk Valley (R. D. Gold et al., 2014) faults (Figure 1). The Southern Walker Lane is composed of predominantly northwest‐striking dextral and normal faults, including the Owens Valley (Beanland & Clark, 1994; Haddon et al., 2016; Kirby et al., 2008; Lee et al., 2001), Fish Lake Valley‐Furnace Creek‐Death Valley (Frankel et al., 2007, 2011; Ganev et al., 2010), and White Mountains (Kirby et al., 2006; Stockli et al., 2003) faults.…”
Section: Regional Contextmentioning
confidence: 99%